The impact of resilience on the experience of parents raising a disabled child - Fitzgibbon, Gabriele (Auckland University of Technology, 2006)
Historically most research on disability and the family has profiled the child’s disability as a tragedy. This ‘tragic’ view has meant that the family was viewed as damaged and in need of being fixed. Research on families with a child with special needs has focused on stressors and families needing support. This pilot study adopted an interpretivist and participatory stance, giving parents a voice. It was positive in its viewpoint, looking at the resilience within the family, particularly the meaning resilience has for them, not at any deficit. As such it sought to give a different focus then most other research to date has done. Participants were 3 mothers of severely disabled children. The findings showed themes of “making sense”, “being yourself” and “being in control”. Participants believed that resilience helps them make sense of their life, keep a sense of self and gain control over their lives. Ways to improve resilience were also explored. This was a small pilot study for a dissertation requirement. Further research exploring more fully the meaning resilience has for parents of disabled children could yield more information and aid the understanding for practitioners involved in the field of disability and be of help to other parents.
Keywords: Parents of children with disabilities; Children with disabilities; Disabilities